PRODUCT PRIVATE LABELS BRANDS SEBAGAI ALTERNATIF MERAIH KONSUMEN PADA PERUSAHAAN RITEL - Susanti, Retno (JURNAL EKONOMI DAN KEWIRAUSAHAAN, 2012)
ABSTRACT In the world of retailing, retailers compete by performing a variety of strategies, which are now commonplace, Private Label Brands / PLBs, this brand of products designed and developed using the name of the retailer in question and only sold by the company , is replaced with a brand in other stores so that helps retailers in controlling the flow of consumer loyalty and establish a store and a project "at a lower price image" of retailers and manufacturers improve bergaining power of national brands. Â  Keywords: Private Label Brands, retailing, consumer